Valuation and Management of Wetland Ecosystem: a Case Study of Pong Dam in Himachal Pradesh. - Prasher, R.S., Negi, Y.S. and Vijay Kumar (2006)
The present paper reviews recent developments in methodology for valuing the role of wetlands in supporting economic activity. The study brings out several issues related to conservation and management of the Pong Dam wetland. For the protection of aquatic biodiversity of the wetland, integrated management plans are required. The main conservation problem being faced by the wetlands is related to increasing siltation from catchment areas. Similarly, the management of weeds for enhancement of fishery resources of wetlands as well as the restoration and conservation of biodiversity of the ecosystems is another important issue. The annual flow value of ecological functions of the Pong Dam wetland is quite substantial. This value is much higher than the returns on alternative uses. Therefore, the conservation of this wetland becomes a pre-requisite. Since, the wetland is habitat to a large number of migratory birds, as such, peoples’ willingness to pay for the preservation of biodiversity is also high. Hence, wetland preservation needs an additional attention.